2018
DOI: 10.3168/jds.2018-14753
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Somaticell, California Mastitis Test, and microbiological examination of composite milk to detect Streptococcus agalactiae intramammary infections

Abstract: The objectives of this study were to estimate the accuracy of Somaticell (Idexx Laboratories Inc., Westbrook, ME), California Mastitis Test (CMT), and microbiological examination of composite milk (MEC) to diagnose Streptococcus agalactiae intramammary infections (IMI), and to assess the agreement between Somaticell and CMT to detect these infections. A secondary objective was to estimate quarter- and cow-level prevalence of S. agalactiae IMI in the herds included in the study. Seven farms were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(35 reference statements)
0
22
0
4
Order By: Relevance
“…Reagents were prepared in distilled water. In the study, 250 milk samples were screened for the detection of mastitis by surf field mastitis test [20]. Mastitic milk samples were screened for the isolation of E. coli on the MacConkey agar media.…”
Section: Sampling and Isolation Of Mastitis Causing E Coli Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reagents were prepared in distilled water. In the study, 250 milk samples were screened for the detection of mastitis by surf field mastitis test [20]. Mastitic milk samples were screened for the isolation of E. coli on the MacConkey agar media.…”
Section: Sampling and Isolation Of Mastitis Causing E Coli Strainsmentioning
confidence: 99%
“…Preparation of CS-NPs. CS-NPs were prepared using ionic gelation process with few modi cations [20]. Two solutions were synthesized; (1) Chitosan (CS solution A) and (2) tripolyphosphate (TPP solution B) ( Figure 1).…”
Section: 42mentioning
confidence: 99%
“…On the other hand, MALDI-TOF-MS-based peptide profiling experiments indicated that all fragments from serum amyloid A3, i.e., (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), were down-represented in subclinical and clinical mastitis goat milk samples, notwithstanding their SCC value, thus suggesting reduced proteolysis of this protein after disease outcome. Variably represented fragments originating from proteolysis of serum amyloid A have already been reported in bovine milk from an experimental model of Streptococcus uberis mastitis [45], but none of the previously ascertained molecules matched the ones described here for infected goat milk.…”
Section: Maldi-tof-ms Peptide Profilingmentioning
confidence: 99%
“…In the above-mentioned context, clinical observation, California mastitis test and white side test were the main field diagnostic tools used for mammary inflammation detection in bovine and goat, whereas culture and isolation were laboratory-based methods [23][24][25]. However, the outcome and interpretation of these diagnostic tests were neither reliable nor specific or confirmatory [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation